Common polymorphisms within the NR4A3 locus, encoding the orphan nuclear receptor Nor-1, are associated with enhanced β-cell function in non-diabetic subjects - Kuusisto Johanna; Machicao Fausto; Stefan Norbert; Gallwitz Baptist; Ranta Felicia; Ullrich Susanne; Kirchhoff Kerstin; Schäfer Silke A; Stančáková Alena; Staiger Harald; Weyrich Peter; Laakso Markku; et al. (BMC, 2009)
Abstract Background Neuron-derived orphan receptor (Nor) 1, nuclear receptor (Nur) 77, and nuclear receptor-related protein (Nurr) 1 constitute the NR4A family of orphan nuclear receptors which were recently found to modulate hepatic glucose production, insulin signalling in adipocytes, and oxidative metabolism in skeletal muscle. In this study, we assessed whether common genetic variation within the NR4A3 locus, encoding Nor-1, contributes to the development of prediabetic phenotypes, such as glucose intolerance, insulin resistance, or β-cell dysfunction. Methods We genotyped 1495 non-diabetic subjects from Southern Germany for the five tagging single nucleotide polymorphisms (SNPs) rs7047636, rs1526267, rs2416879, rs12686676, and rs10819699 (minor allele frequencies ≥ 0.05) covering 100% of genetic variation within the NR4A3 locus (with D' = 1.0, r2 ≥ 0.9) and assessed their association with metabolic data derived from the fasting state, an oral glucose tolerance test (OGTT), and a hyperinsulinemic-euglycemic clamp (subgroup, N = 506). SNPs that revealed consistent associations with prediabetic phenotypes were subsequently genotyped in a second cohort (METSIM Study; Finland; N = 5265) for replication. Results All five SNPs were in Hardy-Weinberg equilibrium (p ≥ 0.7, all). The minor alleles of three SNPs, i.e., rs1526267, rs12686676, and rs10819699, consistently tended to associate with higher insulin release as derived from plasma insulin at 30 min(OGTT), AUCC-peptide-to-AUCGluc ratio and the AUCIns30-to-AUCGluc30 ratio with rs12686676 reaching the level of significance (p ≤ 0.03, all; additive model). The association of the SNP rs12686676 with insulin secretion was replicated in the METSIM cohort (p ≤ 0.03, additive model). There was no consistent association with glucose tolerance or insulin resistance in both study cohorts. Conclusion We conclude that common genetic variation within the NR4A3 locus determines insulin secretion. Thus, NR4A3 represents a novel candidate gene for β-cell function which was not covered by the SNP arrays of recent genome-wide association studies for type 2 diabetes mellitus.